![5-2\, sinx\cdot cosx-5(sinx-cosx)=0\\\\Zamena:\; \; t=sinx-cosx\; ,\\\\t^2=(sinx-cosx)^2=sin^2x+cos^2x-2\, sinx\cdot cosx=1-2\. sinx\cdot cosx\; \to \\\\2\, sinx\cdot cosx=1-t^2\\\\5-(1-t^2)-5t=0\\\\5-1+t^2-5t=0\\\\t^2-5t+4=0\; \; ,\; \; t_1=1\; ,\; t_2=4\; \; (teorema\; Vieta)\\\\a)\; \; sinx-cosx=1\; \; \to \; \; sinx-sin(\frac{\pi }{2}-x)=1\; ,\\\\2sin\frac{x-(\frac{\pi}{2}-x)}{2}\cdot cos\frac{x+(\frac{\pi}{2}-x)}{2}=1\\\\2sin(x-\frac{\pi}{4})\cdot cos\frac{\pi}{4}=1\\\\2sin(x-\frac{\pi }{4})\cdot \frac{\sqrt2}{2}=1 5-2\, sinx\cdot cosx-5(sinx-cosx)=0\\\\Zamena:\; \; t=sinx-cosx\; ,\\\\t^2=(sinx-cosx)^2=sin^2x+cos^2x-2\, sinx\cdot cosx=1-2\. sinx\cdot cosx\; \to \\\\2\, sinx\cdot cosx=1-t^2\\\\5-(1-t^2)-5t=0\\\\5-1+t^2-5t=0\\\\t^2-5t+4=0\; \; ,\; \; t_1=1\; ,\; t_2=4\; \; (teorema\; Vieta)\\\\a)\; \; sinx-cosx=1\; \; \to \; \; sinx-sin(\frac{\pi }{2}-x)=1\; ,\\\\2sin\frac{x-(\frac{\pi}{2}-x)}{2}\cdot cos\frac{x+(\frac{\pi}{2}-x)}{2}=1\\\\2sin(x-\frac{\pi}{4})\cdot cos\frac{\pi}{4}=1\\\\2sin(x-\frac{\pi }{4})\cdot \frac{\sqrt2}{2}=1](https://tex.z-dn.net/?f=5-2%5C%2C%20sinx%5Ccdot%20cosx-5%28sinx-cosx%29%3D0%5C%5C%5C%5CZamena%3A%5C%3B%20%5C%3B%20t%3Dsinx-cosx%5C%3B%20%2C%5C%5C%5C%5Ct%5E2%3D%28sinx-cosx%29%5E2%3Dsin%5E2x%2Bcos%5E2x-2%5C%2C%20sinx%5Ccdot%20cosx%3D1-2%5C.%20sinx%5Ccdot%20cosx%5C%3B%20%5Cto%20%5C%5C%5C%5C2%5C%2C%20sinx%5Ccdot%20cosx%3D1-t%5E2%5C%5C%5C%5C5-%281-t%5E2%29-5t%3D0%5C%5C%5C%5C5-1%2Bt%5E2-5t%3D0%5C%5C%5C%5Ct%5E2-5t%2B4%3D0%5C%3B%20%5C%3B%20%2C%5C%3B%20%5C%3B%20t_1%3D1%5C%3B%20%2C%5C%3B%20t_2%3D4%5C%3B%20%5C%3B%20%28teorema%5C%3B%20Vieta%29%5C%5C%5C%5Ca%29%5C%3B%20%5C%3B%20sinx-cosx%3D1%5C%3B%20%5C%3B%20%5Cto%20%5C%3B%20%5C%3B%20sinx-sin%28%5Cfrac%7B%5Cpi%20%7D%7B2%7D-x%29%3D1%5C%3B%20%2C%5C%5C%5C%5C2sin%5Cfrac%7Bx-%28%5Cfrac%7B%5Cpi%7D%7B2%7D-x%29%7D%7B2%7D%5Ccdot%20cos%5Cfrac%7Bx%2B%28%5Cfrac%7B%5Cpi%7D%7B2%7D-x%29%7D%7B2%7D%3D1%5C%5C%5C%5C2sin%28x-%5Cfrac%7B%5Cpi%7D%7B4%7D%29%5Ccdot%20cos%5Cfrac%7B%5Cpi%7D%7B4%7D%3D1%5C%5C%5C%5C2sin%28x-%5Cfrac%7B%5Cpi%20%7D%7B4%7D%29%5Ccdot%20%5Cfrac%7B%5Csqrt2%7D%7B2%7D%3D1)
1\; \; \to \; \; net\; kornej\; ,\; t.k.\; |sin(x-\frac{\pi}{4})|\leq 1\\\\Otvet:\; \; x=\frac{\pi}{4}+(-1)^{n}\cdot\frac{\pi }{4}+\pi n\; ,\; n\in Z" alt="sin(x-\frac{\pi}{4})=\frac{\sqrt2}{2}\\\\x-\frac{\pi}{4}=(-1)^{n}\cdot \frac{\pi}{4}+\pi n\; ,\; n\in Z\\\\x=\frac{\pi }{4}+(-1)^{n}\cdot \frac{\pi }{4}+\pi n=\left [ {{\pi n\; ,\; esli\; n=2k-1\; ,\; k\in Z} \atop {\frac{\pi}{2}+\pi n\; ,\; esli\; n=2k\; ,\; k\in Z}} \right. \\\\b)\; \; sinx-cosx=4\\\\2sin(x-\frac{\pi }{4})\cdot \frac{\sqrt2}{2}=4\\\\sin(x-\frac{\pi}{4})=2\sqrt2>1\; \; \to \; \; net\; kornej\; ,\; t.k.\; |sin(x-\frac{\pi}{4})|\leq 1\\\\Otvet:\; \; x=\frac{\pi}{4}+(-1)^{n}\cdot\frac{\pi }{4}+\pi n\; ,\; n\in Z" align="absmiddle" class="latex-formula">
![\star \; \; cosx=sin(\frac{\pi}{2}-x)\; \; \star \\\\\star sinx-siny=2sin\frac{x-y}{2}\cdot cos\frac{x+y}{2}\; \; \star \star \; \; cosx=sin(\frac{\pi}{2}-x)\; \; \star \\\\\star sinx-siny=2sin\frac{x-y}{2}\cdot cos\frac{x+y}{2}\; \; \star](https://tex.z-dn.net/?f=%5Cstar%20%5C%3B%20%5C%3B%20cosx%3Dsin%28%5Cfrac%7B%5Cpi%7D%7B2%7D-x%29%5C%3B%20%5C%3B%20%5Cstar%20%5C%5C%5C%5C%5Cstar%20sinx-siny%3D2sin%5Cfrac%7Bx-y%7D%7B2%7D%5Ccdot%20cos%5Cfrac%7Bx%2By%7D%7B2%7D%5C%3B%20%5C%3B%20%5Cstar)